Comprehensive intellectual capital management : step-by-step - Al-Ali, Nermien (Wiley, 2003)
An authoritative resource on managing intellectual capital. Given increased appreciation of intellectual property as an integral value driver in the knowledge economy, most companies have implemented programs to manage their intellectual property. Comprehensive Intellectual Capital Management: Step-by-Step explains the fundamentals, practices, and models of intellectual capital management (ICM), providing a business-oriented, critical review of the definitions, practices, tools, and models that are available today.